Exploring the Need for “Omah Baskara” a Local Wisdom-Based Learning Media for Teaching East Java’s Cultural Diversity - Rizki Farista Sari; Kharisma Eka Putri; Sulistiono Sulistiono (Kognisi : Jurnal Penelitian Pendidikan Sekolah Dasar, 2026)
Learning activities in Natural and Social Sciences at the elementary school level still make limited use of local wisdom-based learning media. Most existing learning media do not incorporate cultural elements from students' surrounding environments, highlighting the need for a needs analysis of local wisdom-based learning media. This study aimed to analyze the need for the "Omah Baskara" local wisdom-based learning media for teaching East Java's cultural diversity in elementary schools. The study employed a mixed-methods approach using a convergent triangulation design. Data were collected through questionnaires, observations, and interviews and analyzed using descriptive quantitative and qualitative techniques. The participants consisted of 30 fourth-grade students from SD Negeri Mrican 1, Kediri City. The findings revealed that 77% of the students experienced difficulties in learning Natural and Social Sciences, while 73% reported difficulty understanding the topic of East Java's cultural diversity. In addition, 80% of the students expressed interest in using learning media integrated with educational games, and 83% preferred concrete learning media equipped with educational games. Furthermore, 87% of the students agreed to use the "Omah Baskara" local wisdom-based learning media. These findings indicate that developing the "Omah Baskara" local wisdom-based learning media is necessary to support more contextual cultural diversity learning that is aligned with the needs of elementary school students.